Evaluation of gamma-ray and neutron shielding features of heavy metals doped Bi2O3-BaO-Na2O-MgO-B2O3 glass systems - Sayyed, M. I.; Ashok Kumar,; Tekin, H. O.; Kaur, Ramandeep; Singh, Mandeep; Agar, O.; Khandaker, Mayeen Uddin * (Elsevier, 2020)
Recognizing the vast uses of radioactive sources in several sectors such as industry, medicine, agriculture, development of effective radiation shielding material finds great significance. Present work is aimed to explore potential glass based material for neutron and gamma ray shielding applications. In the present study, several borate glasses with composition of (20 + x) Bi2O3–20BaO–10Na2O–10MgO–(40-x) B2O3 (where x = 0, 5, 10, 15 and 20 mol%) were successfully synthesized via melt-quenching method, and evaluated their gamma-ray and neutron shielding features. The densities of the studied glasses are increased with the addition of Bi2O3 content. The non-existence of any sharp peak in X-ray diffraction spectra confirms the amorphous nature of the glasses. Fourier transform infrared spectroscopy gives the necessary information regarding the structure of the glasses. The optical band gap for both direct and indirect transitions decreases from 2.905 to 2.806 eV and 2.661 to 2.536 eV as B2O3 replaced with Bi2O3. Some quantities namely mass attenuation coefficients , half-value layer (HVL), mean free path (MFP), macroscopic effective removal cross sections (ΣR) and transmission factor (TF) have been studied theoretically and computationally for gamma-ray and neutron shielding characteristics. The correlation coefficient (R2) values between the XCOM and MCNPX results of all the glasses were found to be almost 1. According to our results, Bi40B20 sample with the highest amount of Bi2O3 has the lowest MFP and TF values, and this suggested that the gamma and neutron shielding performances of the Bi2O3-BaO-Na2O-MgO-B2O3 glasses are improved with the addition of Bi2O3 content.